Tibial Intramedullary Interlocking Nail Without Imaging - Farhoud, Amir Reza; Dehghani Firoozabadi, Mohammad Javad; Yaseen Khan, Furqan Mohammed; Nouroozi, Hamed; Ghadimi, Ehsan (Journal of orthopedic & spine trauma, 2018)
Tibia is one of the most common fractured long bone, which occurs most often in young people following high-energy trauma. Gold standard treatment of tibial diaphysis fractures is currently intramedullary nailing. In this study, we intend to examine the results of treatment of tibia diaphysis fractures with intramedullary interlocking nail without use of imaging (C-Arm) during surgery. In this cross-sectional study, 43 patients (36 males and 7 females with an average age of 31 years) were included, 40% were open fractures and 60% were closed. Just postoperatively, 12% of the cases had a problem with length and placement of nail and screws. A total of 18% had rotational deformity (78% less than 5 degrees) and 5% had only mild varus or apex anterior deformity. In cases where imaging during surgery is not possible for any reason, the use of intramedullary nailing along with distal jig could be performed for tibial shaft fractures.